2012
DOI: 10.1177/0954410012461745
|View full text |Cite
|
Sign up to set email alerts
|

Re-entry trajectory optimization using an hp-adaptive Radau pseudospectral method

Abstract: Aiming at increasing the convergence rate and the accuracy simultaneously, an hp-adaptive Radau pseudospectral method is presented to generate a re-entry launch vehicle's optimal re-entry trajectory. The method determines the number of mesh intervals, the width of the each mesh interval, and the degree of the polynomial in each mesh interval iteratively until a user-specified error tolerance is satisfied. In regions of relatively high curvature, convergence is achieved by dividing a segment into more mesh inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Several extensions of the hp-adaptive pseudospectral method have been used in the reentry trajectory optimization for CAVs and RLVs [46,[63][64][65]. The costate estimation in optimal control problems also uses hp-method [66].…”
Section: Fig 6 Comparisons Of Dps and Cps For The H-methods And P-methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several extensions of the hp-adaptive pseudospectral method have been used in the reentry trajectory optimization for CAVs and RLVs [46,[63][64][65]. The costate estimation in optimal control problems also uses hp-method [66].…”
Section: Fig 6 Comparisons Of Dps and Cps For The H-methods And P-methodsmentioning
confidence: 99%
“…Recent work also showed that the hp-adaptive method demonstrates faster computation time than the traditional pseudospectral methods [46]. A tradeoff between the number of collocation points, grid iterations, and mesh intervals may notably save the computation time.…”
Section: Rapid Trajectory Optimizationmentioning
confidence: 97%
See 2 more Smart Citations
“…Then the optimal problem is transcribed to a normal nonlinear programming (NLP) problem, in which variables to be optimized are the coefficient of basis functions [6]. Because there are numerous well-developed software package(e.g.…”
Section: Introductionmentioning
confidence: 99%